Evaluating the Effect of Live Brine Shrimp (Artemia franciscana) on Growth Performance in Ornamental Fish, Cyprinus rubrofuscus (Lacepede, 1803) - M. V., Aiswarya; S., Mary Mettilda Bai; R., Siva Santhiya; J., Vinoliya Josephine Mary; T., Citarasu; G., Uma; J. R., Anusha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Feeding is a critical factor for both cultured and ornamental fish species. This study aimed to evaluate the effects of live brine shrimp (Artemia franciscana) on the growth and biochemical composition of fish. In the present study, sixty days feeding trail was conducted on the growth performance of ornamental fish, koi carp (Cyprinus rubrofuscus). The type of food such as live feed, nutrient-enriched prepared feed and commercial feed exerted a significant impact on the growth and body composition of fish. The specific growth rate is high in live brine shrimp fed fishes followed by prepared food. After 60 days experiment showed that the maximum length and weight of live brine shrimp fed fishes were 7.5 ± 0.9 cm and 5.3 ± 1.7 gm, respectively. The survival rates of the fish were 100 % under all feeding groups. The biochemical profiles of the fish varied significantly between the different feeding regimes. These results suggest that live feed is more effective than pelletized feed for ornamental fish culture.